Вычислить предел последовательности - пример

Подождите несколько секунд до окончания загрузки формул! (Подробнее)

Задание:

Вычислить $${\lim_{{n}\to {+\infty}}\left({\sqrt{3+2 n}-\sqrt{-1+n}}\right)}$$

Решение:


$${\lim_{{n}\to {+\infty}}\left({\sqrt{3+2 n}-\sqrt{-1+n}}\right)}$$ = $${\lim_{{n}\to {+\infty}}\left({\frac{{\left({\sqrt{3+2 n}-\sqrt{-1+n}}\right)\cdot \left({\sqrt{3+2 n}+\sqrt{-1+n}}\right)}}{{{1}\cdot \left({\sqrt{3+2 n}+\sqrt{-1+n}}\right)}}}\right)}$$ = $${\lim_{{n}\to {+\infty}}\left({\frac{4+n}{\sqrt{3+2 n}+\sqrt{-1+n}}}\right)}$$ = $${\lim_{{n}\to {+\infty}}\left({\frac{1+4 \frac{1}{n}}{\sqrt{-\frac{1}{{{n}^{2}}}+\frac{1}{n}}+\sqrt{3 \frac{1}{{{n}^{2}}}+2 \frac{1}{n}}}}\right)}$$ = $$\infty$$

Ответ:

$${{{\lim_{{n}\to {+\infty}}\left({\sqrt{3+2 n}-\sqrt{-1+n}}\right)}}={\infty}}$$